2005
DOI: 10.1159/000085524
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Physiological Properties of Porcine Surfactant Enriched with Polymyxin B

Abstract: Objective: We examined whether the biophysical and physiological properties of Curosurf® were improved by the cyclic amphipathic decapeptide polymyxin B (PxB). Methods: Curosurf was diluted to 1–5 mg/ml with PxB added at 1, 2 or 3% (w/w). Albumin was added at 40 mg/ml. Minimum surface tension (γmin) during surface compression was determined for each mixture with pulsating bubble. Immature newborn rabbits were treated with 2.5 ml/kg of Curosurf 80 mg/ml, or Curosurf 32 mg/ml with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
(30 reference statements)
1
22
1
Order By: Relevance
“…In the absence of LPS in vitro, the surfactant/PxB preparations showed increased resistance to surfactant inactivation with albumin or meconium (5,20). However, in the present investigation, addition of PxB resulted only in an inconsistent improvement in compliance (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 47%
“…In the absence of LPS in vitro, the surfactant/PxB preparations showed increased resistance to surfactant inactivation with albumin or meconium (5,20). However, in the present investigation, addition of PxB resulted only in an inconsistent improvement in compliance (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 47%
“…In the absence of meconium, PxB significantly reduced static surface tension only at 2.5 mg/mL Curosurf in the Wilhelmy balance, whereas no improvement was seen at 5 mg/mL or when identical samples were tested for static or dynamic surface tension in the PBS. Calkovska et al (19) found improved dynamic surface activity after addition of 2% PxB to Curosurf 2 mg/mL. We used slightly higher Curosurf concentrations and found, even without addition of PxB, ␥ min Ͻ3 mN/m.…”
Section: Polymyxin B Surfactant and Meconiummentioning
confidence: 73%
“…Calkovska et al (19) suggested an increased resistance of Curosurf to albumin-induced inactivation in vitro after addition of PxB 2% (wt/wt), corresponding with 2-4 mg/kg body weight. For aerosolized free PxB, a maximum dose of 2.5 mg/kg/d divided in four doses is recommended for adults with normal renal clearance (35).…”
Section: Polymyxin B Surfactant and Meconiummentioning
confidence: 99%
“…By addition of different components such as dextran [45,46] , polyethyleneglycol [46] , hyaluronan [47] or polymyxin [48] to surfactant preparations, the inhibition can be counteracted as shown by both in vitro and in vivo experiments. Furthermore, recent observations in our laboratory have shown that the function of SP-B can be mimicked in vitro by polymyxin B, a structurally different acylated peptide, which cross-links phospholipid vesicles by ionic interactions.…”
Section: Resistance To Surfactant Inactivationmentioning
confidence: 99%
“…Furthermore, recent observations in our laboratory have shown that the function of SP-B can be mimicked in vitro by polymyxin B, a structurally different acylated peptide, which cross-links phospholipid vesicles by ionic interactions. Addition of 2% (w/w) of polymyxin B to the surfactant preparation increased the resistance of pulmonary surfactants to inactivation and improved their surface properties [48] . These data indicate that one of the functions of SP-B is to cross-link lipid vesicles and that this effect can be mimicked by a rather simple peptide.…”
Section: Resistance To Surfactant Inactivationmentioning
confidence: 99%